Desain Simulasi Maksimum Power Point Tracking Metode P&O Pada Panel Surya Di Azzahra Hidroponik Juata Tarakan - Abil Huda; Wahyudi Siraju (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Solar panels are electricity generators that utilize solar energy. One of them is the Azzahra Hydroponic solar panel with a capacity of 200 Wp which has a non-linear output. According to Amri, (2015) this is due to the changing conditions of the sun. To solve the non-linear problem of solar panels, there are 2 types of controllers, namely PWM and MPPT. This study uses the Perturb Observe (PO) method because this method is simpler, has efficiency and a high level of accuracy compared to other methods (Kesler, 2016). Under conditions of intensity S= 1000 and temperature T = 40°, Pmax is 201.5 W, Po is 201.1 W and the time required for MPPT to track is 0.003 seconds, at S=500 T=25, Pmax= 97 ,7 W and Po = 96.4 W and the time required is 0.006 seconds. And in the condition S = 100 T = 10 obtained Pmax = 9.4 W, Po = 9.3 W and the time required for MPPT to track is 0.04 seconds. Based on the simulation results, it can be concluded that the maximum power point tracking (MPPT) simulation design using the perturb and observe (PO) method was successful and MPPT was able to track the maximum power on Azzahra Hydroponic solar panels under conditions of varying intensity and temperature.